Synthesis, Characterization, and Application of Rubber Fruit Shell as an Adsorbent for Phosphate Removal in Real Grey Water - Muhammad Naswir; Yudha Gusti Wibowo; Winny Laura (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The washing waste from the laundry industry contains phosphate that can pollute the environment. Multiple efforts have been made but have not reached the small to medium-scale laundry industry; this happens because of the high cost of technology. In this paper, the sorption process by rubber fruit shells successfully reduced the pollutants parameter from greywater. This research has succeeded in creating an adsorbent with raw rubber fruit shell waste; studies on manufacturing techniques, adsorbent characteristics, ability to reduce phosphate content, and adsorption isotherm models are well described. This study also promotes the utilization of rubber shell waste that has not been utilized properly. Adsorbents derived from rubber fruit shells reduced phosphate levels by up to 98% by adding 0.5 g of adsorbent to 100 mg/L of phosphate for 60 minutes. The appropriate adsorption isotherm model in this study is the Freundlich isotherm model.